HUBUNGAN TINGKAT KEPERCAYAAN MASYARAKAT PADA CITIZEN JOURNALISM TERHADAP TINGKAT KONSUMSI BERITA DI MEDIA MAINSTREAM - Valeria, Vynski; Gelgel, Ni Made Ras Amanda; Joni, I Dewa Ayu Sugiarica; Damasemil, Calvin (E-Jurnal Medium; Vol 3 No 2 (2022): Jurnal Ilmu Komunikasi Vol 3 No 2 Tahun 2022, 2023)
This study explains how the relationship between the level of public trust in citizen journalism and the level of news consumption in mainstream media where journalists in mainstream media have professional ethics, namely the journalistic code of ethics. This study uses an explanative quantitative method.The number of samples in this study were 70 respondents. The respondents in this study were the people of Denpasar city with an age range of 18 to 25 years. In proving and analyzing the data, the researcher used a simple linear regression statistical test. The results showed that there was a relationship between the level of trust and the level of news consumption. These results indicate that the relationship between the level of public trust in citizen journalism and the level of news consumption in mainstream media is 34.2%. Keywords : Trust level, Citizen Journalism, News consumption rate, Mainstream Media .